Equity ownership concentrations impact on corporate internal control: the moderating effects of female directors and board compensation - Ong, Tze San; Zhou, Jing; Teh, Boon Heng; Di Vaio, Assunta (Springer, 2023)
By promoting diversity in equity ownership concentration, strengthening female representation on boards, aligning pay with sustainability goals, and implementing strong internal control processes, companies can integrate sustainable practices into their operations, improve their sustainability performance, and attain long-term environmental and societal health. Therefore, this study examined the relationship between ownership concentration and internal control through the sustainability lens, specifically focusing on the moderating effects of female directors and board compensation. Data from a sample of 1609 A-share listed businesses in Shanghai and Shenzhen between 2012 and 2021 were analyzed. The findings from the fixed effects model revealed the following: ownership concentration negatively affects internal control; the number of female directors positively influences internal control; female directors actively moderate the relationship between ownership concentration and internal control; and board compensation enhances the effectiveness of internal control. These insights provide valuable data for businesses to enhance their internal control systems, appoint key personnel, and advance their sustainability goals. This study suggests that linking board characteristics to corporate internal control can lead to strengthened sustainable objectives. It also incentivizes directors to prioritize and integrate sustainability concerns in their decision-making. Furthermore, by ensuring that compensation reflects sustainability performance, firms can cultivate a sustainability-based culture and drive effective internal controls that support sustainable practices, ultimately contributing to long-term environmental and social well-being.